Effect of animal manure-based substrates on the emergence and vegetative growth of fodder oats (Avena sativa L.) - Canales Gutiérrez, Angel; Sucari Turpo, Guadalupe (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Oats (Avena sativa L.) are an annual forage grass of great current and potential importance in agricultural development. The objective was to determine the effect of animal manure-based substrates on the emergence and vegetative growth (stem height and leaf length) of forage oats (Avena sativa L.) in relation to organic amendments (chicken-cuy, cattle-sheep, llama-alpaca) over time. Growth variables were measured every ten days up to 60 days. A completely randomised experimental design was used; each treatment consisted of five replicates of ten seeds each. Analysis of variance (ANDEVA), Tukey's multiple comparison and regression and correlation analysis were performed. Both stem height and leaf length were higher when the seeds were established on a substrate based on a mixture of cattle and sheep manure and were lower with the llama-alpaca manure mixture. In general, growth expressed in stem height and leaf length increased over time. The application of organic matter of animal origin improves the quality of agricultural soils, which is reflected in plant growth and development.